Potencial de substâncias coloridas produzidas por fungos endofíticos amazônicos para o diagnóstico baciloscópico da tuberculose . - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
Tuberculosis (TB), an infectious disease that occurs in 90% of cases in the lungs, is caused by Mycobacterium tuberculosis. Although TB has been described since antiquity, being diagnosed about 100 years and has treatment from the 40s, is currently still considered a serious public health problem, being reported annually 1.1 million deaths worldwide. Knowing that the cycle of transmission of tuberculosis involving almost exclusively the human, being one of the targets for global TB control is the diagnosis, this being vital to break the chain of transmission. The Global Tuberculosis Control Programmes use bascilloscopies (microscopic detection of bacilli)as their first choice in the diagnosis of pulmonary tuberculosis. However, carbolfucsina, the dye solution used in this method is a toxic carcinogenic compound which contaminates water and endagers human health. In order to verify the potential of coloured substances produced by fungi endophytic filamentous to replace carbolfucsina, endophytes derived from vegetables H. sucuuba , C. multijuga , P. aduncum and S. reticulata were analyized. From 75 isolates, 30 were selected with capacity to produce coloured diffusible substances in solid medium. The culture filtrates were tested in for their ability to stain smears prepared from the standard strain of Mycobacterium tuberculosis H37Rv. Analysis of the staining was performed by bright field and fluorescence microscopy. Fluorescence substances identified as proteins by the Bradford technique, present in 78% of the culture filtrates, enabled the visualization of M. tuberculosis H37Rv. When the culture filtrates were tested with other microorganisms (E. coli ATCC 25922, S. aureus ATCC 25923 and C. albicans ATCC 36232) they were found to be nonspecific for M. tuberculosis. Despite the negative result of the proposed objective, there is potential for fluorescent proteins to be used in monitoring cell, tissue and protein interactions.
Keywords: Substâncias coloridas; Diagnóstico; Tuberculose; Colored substances; Diagnosis; Tuberculosis; CIÊNCIAS BIOLÓGICAS